Analysis of Health Service Quality in the Effort to Ensure Patient Safety at the Community Health Center (Puskesmas) in Bantaeng City, Bantaeng Regency, in 2025 - St. Nurul Aliah Alwy; Westy Tenriawi (Universitas Muhammadiyah Palu, 2025)
Patient safety is one of the indicators of the quality of health services. Patient safety is an important part of improving the quality of services. Bantaeng City Health Center in Bantaeng Regency is one of the health service facilities that implements patient safety efforts as one form of effort to improve the quality of health services as referred to in Law of the Republic of Indonesia Number 36 of 2009. The purpose of this study was to identify the implementation of patient safety efforts at the Bantaeng City Health Center to improve the quality of services. Data collection techniques used were observation, interviews, and literature studies. Data collection was carried out at the Bantaeng City Health Center. The results of data analysis showed that the implementation of patient safety efforts at the Bantaeng City Health Center was adjusted to the Puskesmas accreditation assessment standards. However, in its realization there are still obstacles and shortcomings in meeting the standards for patient safety efforts at the Bantaeng City Health Center, so it is necessary to optimize patient safety efforts from all parties involved. It can be concluded that health centers must provide safe and quality services to create a healthy sub-district.